Self‐reported exercise frequency and PTSD: results from the National Health and Resilience in Veterans Study. (17th October 2020) - Adams, T. G.; Forte, J.; Fogle, B. M.; Southwick, S. M.; Pietrzak, R. H.
Abstract : Objective: Physical exercise may serve as a protective factor for posttraumatic stress disorder (PTSD), but little is known about whether physical exercise is associated with PTSD in population‐based samples of military veterans. Methods: We analyzed cross‐sectional data on the relation between self‐reported physical exercise frequency and the prevalence of probable PTSD in a nationally representative sample of 2832 U.S. military veterans who participated in the National Health and Resilience in Veterans Study. Results: A "U‐shaped" association best explained the relation between self‐reported exercise frequency and the prevalence of probable PTSD. Compared to veterans without probable PTSD, those with probable PTSD were nearly twice as likely to report no weekly exercise (52.3% vs. 29.3%) or daily (7 days/week) exercise (15.2% vs. 8.5%) and were nearly half as likely to report exercising a median of 3.5 days/week (32.6% vs. 62.1%). No exercise was associated with greater severity of emotional numbing and lower severity of anxious arousal symptoms, while daily exercise was associated with greater severity of re‐experiencing symptoms. Conclusions: Results of this study suggest a "U‐shaped" association between self‐reported exercise frequency and the prevalence of probable PTSD among U.S. veterans. Veterans with probable PTSD were more likely than those without probable PTSD to report not exercising at all or exercising every day and were less likely to report exercising 1–6 days per week. Clinical implications of these findings are discussed.